Heat-Killed Enterococcus faecalis Prevents Adipogenesis and High Fat Diet-Induced Obesity by Inhibition of Lipid Accumulation through Inhibiting C/EBP-α and PPAR-γ in the Insulin Signaling Pathway - Lee, Jin-Ho; Woo, Keun-Jung; Kim, Min-Ah; Hong, Joonpyo; Kim, Jihee; Kim, Sun-Hong; Han, Kwon-Il; Iwasa, Masahiro; Kim, Tack-Joong (Nutrients, 2022)
Increasing consumption of food with high caloric density and a sedentary lifestyle have influenced the increasing obesity prevalence worldwide. The recent pandemic has contributed to this problem. Obesity refers to a state in which lipid accumulates excessively in adipocytes and adipose tissues. Dried heat-killed Enterococcus faecalis (EF-2001) prevents allergic mechanisms, inflammation, and tumor progression. In the present study, we investigated the effects of EF-2001 on high fat diet (HFD)-induced obese rats. The degree of obesity in experimental rats was reduced after 6 weeks of oral administration of 3 mg/kg or 30 mg/kg dosages of EF-2001, indicating regulating effects in rats with HFD-induced obesity. We found that EF-2001 decreased the amounts of total cholesterol, triglyceride, and non-high density lipoprotein (HDL) in HFD-induced obese rats. The effects of EF-2001 on 3T3-L1 adipocytes stained with Oil red O stain are shown in reductions of lipid accumulation, respectively. In addition, we examined the relationships between EF-2001 treatment and mechanisms for the insulin signaling of adipogenesis in 3T3-L1 cells. EF-2001 induced down-regulation in phosphorylation of Erk, JNK, and Akt through the inhibition of insulin receptor phosphorylation. EF-2001 inhibits the expressions of C/EBP-α and PPAR-γ, a lipid metabolism-related transcription factor through confocal microscope observation and Western blot on 3T3-L1 adipocytes and HFD-induced obese rats. Based on our results, intake of EF-2001 significantly prevented HFD-induced obesity in rats through inhibition of C/EBP-α and PPAR-γ in the insulin signaling pathway on lipid accumulation.